Perspektif Inovasi Dalam Aplikasi “Dukcapil Dalam Genggaman V.2” Di Dinas Kependudukan Dan Pencatatan Sipil Kota Surakarta - Yudhanto, Bayu Tri; Pramono, Joko; Suhita, Damayanti (Solidaritas, 2024)
The development of Information and Communication Technology (ICT) in Indonesia, driven by Law No. 23 of 2014, has spurred bureaucratic reforms, including in population administration. The city of Surakarta is one of the cities that has successfully implemented E-Government, with the "Dukcapil dalam Genggaman" application as an innovation in public services, making it easier for citizens to manage population documents without having to visit the office. This application serves various needs such as E-KTP, family cards, and birth certificates, with a user satisfaction rate of 93.38%. However, several challenges remain, such as limited socialization, accessibility issues for the elderly, and platform availability only on Android. This study uses a qualitative descriptive method with five indicators from Rogers' theory to analyze this innovation: Relative Advantage, Compatibility, Complexity, Trialability, and Observability. The results indicate that the application provides ease of access, time efficiency, and transparency, but requires further improvement, particularly in user convenience and broader socialization. In conclusion, this application has great potential to improve the quality of public services, but further development and adaptation are needed to achieve optimal benefits. Keywords : E-Government, Surakarta, Dukcapil Dalam Genggaman V.2 Aplication